PERANAN KOORDINASI CAMAT DALAM MENUNJANG KEBERHASILAN PEMBANGUNAN DI WILAYAH KECAMATAN LANGOWAN BARAT - RANTUNG, FRANDY ALVANDO; Pangkey, Masje; Rompas, Sonny (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: success in establishing a town. What’s in the coordination and supervision of the sector. it is, of course, interfere with the process of running programs that have been in the plan. Weak coordination system in the Sub-District Government apparatus into a problem and need to examine again. and from the observations of the author of one of the districts in the Regency of Minahasa Langowan Barat subdistrict, precisely Not optimally cordinated by the Government apparatus. The purpose of this research was to determine the role of the head of the coordination support the success of the Western development in district Langowan Departing from the problem and research objectives, the type of research that is in use is a kind of qualitative research, with observation data retrieval techniques, interviews, library studies and documentation. The results of discussion demonstrating that: head of coordination in the West, already Langowan goes well with good and is in compliance with duty as head of the subdistrict. The apparatus is still lacking resources this is apparent in the level of education is still at domination by the , it graduates have also affected the management of the existing administration in district of Western Langowan supporting facilities in the Office District is still pretty minimal. This can be seen from the lack of vehicle service, so the process of work particularly in the program directly into the field sufficiently slow also facilities such as computers, and the internet at the Office of the district that has not been adequate. Referring to the conclusion above then suggested the role of head of coordination is currently well underway for that require consistency in the conduct of all existing programs. Camat presumably always act firmly but could also consider and hear the right advice from the staff officers, so harmony and harmony in a joint task. In the study permit and presumably training program to the entire Government apparatus in district West langowan So that in carrying out all duties and job bias is more effective the addition of means of transport is very important in that the mobilization and employment particularly work directly into the countryside this is certainly requires an adequate means of transport to be biased work goes well, the addition of computer and ancillary administration tool is also a very important thing, considering so much of his Government duties that require computer and technology tool tools supporting the other. Keywords: The Role Of The Head Of Coordination